Corporate Social Responsibility and Climate Action: Assessing Indonesian Mining Companies’ Contributions to SDG 13 - Wahyu Endah Christiani Putri; Akhmad Zamroni; Roel F. Ceballos; Ronnel C. Nolos (Magister Program of Material Science, Graduate School of Universitas Sriwijaya, 2026)
This study examines how Indonesian mining companies incorporate climate action within their corporate social responsibility (CSR) strategies, with a particular focus on their contributions to Sustainable Development Goal (SDG) 13. Using qualitative content analysis of ten publicly available CSR and sustainability reports, the study identifies recurring themes in corporate disclosures, including operational activities, environmental performance data, target-setting, and collaborative initiatives. The findings reveal both progress and gaps in aligning mining practices with national and international climate objectives. Four thematic areas emerge, including (1) operational decarbonization efforts that increasingly combine low-carbon technologies with nature-based solutions (NbS), although their effectiveness is rarely assessed through standardized indicators; (2) responsibility framing and measurable targets that show greater alignment with frameworks such as the Paris Agreement and Indonesia’s Nationally Determined Contributions, yet governance and assurance mechanisms remain underdeveloped, raising concerns of potential greenwashing; (3) while disclosure of environmental data has improved, comparability across firms is constrained by inconsistent adoption of metrics and limited integration of Life Cycle Assessment (LCA); and (4) climate-related risks are widely acknowledged, with firms outlining resilience strategies and engaging in multi-stakeholder partnerships to enhance adaptive capacity. Overall, Indonesian mining companies demonstrate a growing recognition of their role in climate action. However, advancing their contribution to SDG 13 requires systematic evaluation of NbS, stronger ESG governance and accountability, broader institutionalization of LCA, and deeper stakeholder engagement. These improvements are essential to ensure CSR initiatives deliver substantive, measurable, and socially inclusive climate outcomes.